Characteristics of the School Education System in England - Shozoda Muftillayeva (Procedia of Social Sciences and Humanities, 2022)
Today, the United Kingdom is one of the leaders in the quality and level of education. There are several reasons for this level of education. To understand these reasons, we must first look at the history of education in England. Education in England in the Middle Ages was very different from what it is today. only church members were engaged.